Piezo-tribo dual effect hybrid nanogenerators for health monitoring - Shawon, Sk Md Ali Zaker; Sun, Andrew Xu; Vega, Valeria Suarez; Chowdhury, Brishty Deb; Tran, Phong; Carballo, Zaida D.; Tolentino, Jim Aica; Li, Jianzhi; Rafaqut, Muhammad Sufian; Danti, Serena; Uddin, M. Jasim (Nano energy, 2021)
Over the years, nanogenerators for health monitoring have become more and more attractive as they provide a cost-effective and continuous way to successfully measure vital signs, physiological status, and environmental changes in/around a person. Using such sensors can positively affect the way healthcare workers diagnose and prevent life-threatening conditions. Recently, the dual piezo-tribological effect of hybrid nanogenerators (HBNGs) have become a subject of investigation, as they can provide a substantial amount of data, which is significant for healthcare. However, real-life exploitation of these HBNGs in health monitoring is still marginal. This review covers piezo-tribo dual-effect HBNGs that are used as sensors to measure the different movements and changes in the human body such as blood circulation, respiration, and muscle contractions. Piezo-tribo dual-effect HBNGs are applicable within various healthcare settings as a means of powering noninvasive sensors, providing the capability of constant patient monitoring without interfering with the range of motion or comfort of the user. This review also intends to suggest future improvements in HBNGs. These include incorporating surface modification techniques, utilizing nanowires, nanoparticle technologies, and other means of chemical surface modifications. These improvements can contribute significantly in terms of the electrical output of the HBNGs and can enhance their prospects of applications in the field of health monitoring, as well as various in vitro/in vivo biomedical applications. While a promising option, improved HBNGs are still lacking. This review also discusses the technical issue which has prevented so far, the real use of these sensors. [Display omitted] •Piezo-tribo dual effect Hybrid Nanogenerators (HNGs) as health monitoring sensors.•HNGs as sensors to measure the different movements and changes in the body.•Application of HNGs as a means of powering noninvasive sensors, and capable of constant patient monitoring.•This review discusses the improvements in terms of the electrical output of the HNGs, their prospects in the field of health monitoring, as well as various in vitro/in vivo biomedical applications.•This review also discusses the technical issue which have prevented so far, the real use of the HNGs as sensors.